IMPLEMENTATION OF SHARIA COMPLIANCE AND GOOD CORPORATE GOVERNANCE AT BANK SYARIAH INDONESIA TEBING TINGGI SUDIRMAN 2 BRANCH OFFICE - Azka Abi Nugraha; Yusrizal; Atika (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2023)
Shariah compliance is an integral aspect of the banking sector's sustainability and is closely linked to good corporate governance. This study aims to analyze the implementation of Shariah compliance and good corporate governance, along with the challenges faced in implementing Shariah compliance and GCG principles at Bank Syariah Indonesia KCP Tebing Tinggi Sudirman 2. The research utilizes a qualitative methodology, with data obtained from primary and secondary sources. Primary data includes the Shariah Supervisory Board, Shariah Audit Committee, and Shariah Investment Committee. Secondary data consists of policy and procedural documents from the Islamic bank, as well as previous research and studies on Shariah compliance and GCG implementation in the Islamic banking sector. Data collection techniques employed in this study encompass interviews and documentation. The findings reveal that the principles of Good Corporate Governance (GCG) at Bank Syariah Indonesia KCP Tebing Tinggi Sudirman 2 encompass transparency, accountability, responsibility, independence, and fairness. Bank Syariah Indonesia KCP Tebing Tinggi Sudirman 2 has implemented Shariah compliance in accordance with the rules and principles of Shariah in every transaction, utilizing appropriate contracts such as murabahah, musyarakah, mudarabah, ijarah, rahn, and in fund mobilization, mudarabah and wadi'ah contracts are utilized. The bank's products have received approval from the National Shariah Board-Indonesian Ulama Council (DSN-MUI), the authorized institution for issuing Shariah fatwas. The implementation of Shariah compliance at Bank Syariah Indonesia KCP Tebing Tinggi Sudirman 2 involves transaction procedures based on Shariah principles, internal supervision, collaboration with DSN-MUI, employee training and awareness enhancement, as well as external audits aimed at ensuring the bank's compliance with Shariah principles